Endoscopic full-thickness plication for the treatment of gastroesophageal reflux disease: A systematic review and meta-analysis - Niu, Chengu; Zhang, Jing; Iyer, Charoo; Saeed, Hasaan; Zhu, kaiwen; Elkhapery, Ahmed; Okolo, Patrick I (Endoscopy International Open, 2024)
Background and study aims Gastroesophageal reflux disease (GERD) is a widespread chronic gastrointestinal condition with an increasing worldwide prevalence. This research was a systematic review and meta-analysis evaluating the efficacy, safety, and long-term outcomes of endoscopic full-thickness plication (EFTP) for the treatment of GERD.Methods A comprehensive search of databases was conducted for studies published up to April 2023. We included randomized controlled trials (RCTs) and prospective observational studies that examined the use of EFTP in treating GERD among adult patients. We calculated pooled effect estimates using a random-effects model.Results EFTP significantly improved GERD Health-Related Quality of Life (GERD-HRQL) scores at 3-, 6-, and 12-month follow-up intervals. A considerable proportion of patients discontinued proton pump inhibitors, with cessation rates of 59% (95% confidence interval [CI]: 0.47–0.71), 68% (95% CI: 0.58–0.78), and 67% (95% CI: 0.46–0.89,) at 3, 6, and 12 months, respectively. At 3 and 6 months, 61% (95% CI: 0.54–0.68) and 66% (95% CI: 0.56–0.76) of patients experienced ≥50% improvement in GERD-HRQL scores. EFTP demonstrated a favorable safety profile, with a low rate of severe adverse events. We observed a 6.76% reduction (95% CI: –14.53–1.02) in the percentage of time with esophageal pH <4, a decrease in DeMeester scores, and fewer total reflux episodes. The average procedure time was 22.75 minutes (95% CI: 22.03–23.48). Subgroup analyses suggest that both the GERDx system and the NDO Plicator are effective and safe in treating GERD.Conclusions The findings from our study reveal that EFTP is a safe and effective treatment for GERD patients who have not responded adequately to conventional therapies. Given its minimally invasive nature, effectiveness, and limited adverse effects, EFTP emerges as a compelling alternative to conventional surgical procedures.
Keywords: Reflux disease; GI surgery; Endoscopy Upper GI Tract; Motility / achalasia